Performance evaluation in Bluetooth dense piconet areas. - Mazzenga, F.
Bluetooth is a low-cost, short-range wireless technology capable of providing many communication functionalities, ranging from wire replacement to simple personal area networking. In Bluetooth local networking applications, a critical issue still under study is the evaluation of the network performance when multiple piconets are simultaneously active in the same area, thus, causing mutual interference. We provide a closed-form expression for the packet loss probability in Bluetooth dense piconet area accounting for capture effects due to propagation losses. The effectiveness of the proposed approach is assessed by comparing the analytical results with those obtained from Monte Carlo simulations. By considering different scenarios, we show the dependence of results on the geometry and on the characteristics of the environment. It is observed that packet loss probability can significantly change with the position of the reference receiver in the area, as well as with the extension of the piconets area as compared with the coverage area of the receiver. We use the packet loss probability to evaluate the upper and the lower bounds of the network aggregate throughput and the average packet transmission time. Due to propagation effects, large variations of these parameters with the position of the reference receiver in the area are evidenced.
Keywords: Bluetooth dense piconet area; Monte Carlo simulation; Cochannel interference; Packet loss probability; Personal communication network